Analysis on the job training and off the job training to performance through competency in regional water companies in Mojokerto City - Mersiana Varia Juita (Junal Ilmu Manajemen, 2023)
The Regional Drinking Water Company is a company that monopolizes the distribution of water to the community so that it is expected to be able to supply and distribute water according to community needs. Therefore, competent human resources are needed to support performance Regional Drinking Water Company. The decline in the performance of the Mojokerto City Water Supply Company as a whole is largely determined by three performance measurement indicators, namely services, operations and human resources. In the human resources section, the increase in the competence of Regional Drinking Water Company employees from 2017-2022 has experienced a downward trend. These indications show the need for training programs for employees in order to improve employee competence and performance. The purpose of this study was to determine the effect of on the job and off the job training through competence on the performance of employees of the Mojokerto Water Supply Company. The sample in this study used 40 employees of the Regional Drinking Water Company in Mojokerto City. Data analysis used in this study used path analysis. Based on the research results, it can be concluded that on the job training and off the job training have an effect on competency in the Mojokerto Water Supply Company. Whereas on the job training, off the job training and competence affect employee performance. For indirect influence, on the job training and off the job training through competence has a significant influence on the performance of employees in Regional Drinking Water Company in Mojokerto City.